The apologetic meaning of Kant’s "Critique of pure reason" - Victor Lega (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article draws a Christian apologetic conclusion from the transcendental method undertaken by Kant in his work "Critique of Pure Reason". Kant agrees with Hume that the materialistic approach to physics will not be able to fulfill the main task of this science - to explain the existence of cause-and-effect relationships between things and phenomena, expressed in the form of the existence of universal laws of nature and having the form of strict mathematical equations. Solving this problem, Kant came to the conclusion that the laws of nature exist in the human mind in the form of its a priori forms. Kant called this situation the Copernican revolution. However, such a conclusion cannot satisfy a scientist convinced of the objectivity of the laws of nature. The way out of this situation is suggested to us, on the one hand, by the founders of modern science Galileo and Descartes, who showed that the laws of nature exist because they are given to nature by God, and on the other hand, by the great Fathers of the Church, who developed the doctrine of man as the image of God. Thus, it turns out that the laws of nature, established for nature by God, are actually in the human mind, which is the image of the Divine Logos. It turns out that Kant came to the same conclusion as the Christian theologians, only in a philosophical way, showing at the same time the fallacy of materialism